Leptospira induced haemoglobinuric nephrosis in an adult horse and it’s therapeutic management- An uncommon incidence - Saravanan, Subramanian; Chandrasekaran Sundararajan, Rajagopalan; Krishnaswamy, Gopalan Tirumurugaan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Leptospirosis is a zoonosis caused by the spirochete, Leptospira interrogans, affecting various livestock species, including horses. Animals can act as carriers or reservoirs, transmitting the bacteria through urine to humans and thus has a great impact on public health. Worldwide, every year, approximately 1.03 million clinical cases are being reported in humans, leading to 58,900 deaths. Clinical form of leptospirosis in horses is uncommon or rare (Malanova, 2019) and infrequently reported owing to subclinical form of the disease and diagnostic challenges (Verma et al., 2013). The most common manifestation in affected horse is equine recurrent uveitis (ERU) (Gerding and Gilger, 2016), though the disease can cause vasculitis affecting kidneys, liver, central nervous system and genital tract (Divers et al., 2019). Horses acquire leptospirosis through feed or water contaminated with infectious urine and reproductive fluids (Verma et al., 2013) or through the skin. This paper reports an unusual case of equine leptospirosis with haemoglobinuria, it’s diagnosis by microscopic agglutination test and successful therapeutic management.